Earthquake, reconstruction and reform. The brotherhoods of Lima in the face of the earthquake of 1746 - Lévano Medina, Diego (2022)
The earthquake of 1746 is an important milestone in Peruvian historiography because of its transcendence as a telluric movement and above all due to its impact from the economic, political and social points of view in the Peruvian society of the XVIII century. This article aims to provide a new vision through one of the most significant social bodies for the population of Lima at the time: the brotherhood. I address the role played by these corporations in the face of the earthquake and how they were affected materially and spiritually. Besides, how the process of material and administrati-ve reconstruction after the earthquake confronted them with the general reforms of these corporations promoted from the peninsula at the end of the 1750s.